IR spectroscopic measurement of hydrogen production kinetics in methane dry reforming. (19th April 2019) - Ren, Jiazheng; Li, Ming; Lee, Alex Chinghuan; Cheng, Kai; Chen, Yongsheng
Abstract: Dry reforming of methane (DRM) is a reaction that converts two greenhouse gases, CH4 and CO2, to syngas (H2 + CO). Gas chromatography (GC) is almost exclusively used to evaluate catalyst performance. In order to measure the hydrogen production rate with GC, an inert gas with a constant flow rate is usually fed into the system as an internal standard. In this work, an IR spectroscopy-based method is used to achieve the same technical goal with much higher time resolution and much smaller measurement errors. IR measures the molar fractions of CH4, CO2, CO and H2 O in the reaction effluent. By applying general mass balance principle and the relevant reaction stoichiometries, H2 production rate is successfully measured without an internal standard. The results are quite close to those obtained by GC with much higher time resolution, making it possible to observe fast reaction kinetics. Highlights: Hydrogen production rates in DRM were measured without an internal standard. Higher reaction temperature led to higher hydrogen production rate. The IR-based method obtained over 100 times higher time resolution than GC. Accurate IR measurement of CH4 and H2O molar fractions was essential.